GOVERNMENT OF INDIA CENTRAL MARINE FISHERIES RESEARCH STATION MANDAPAM CAMP ANNUAL REPORT OF THE CHIEF RESEARCH OFFICER FOR THE YEAR ENDING 31ST MARCH 1954 - Mandapam, CMFRS (Indian Journal of Fisheries, 2016)
THE year 1953-54 marked further progress in marine fisheries research work carried out at the Headquarters Station at Mandapam, the Sub-Station at Kozhikode and the Research Units at Karwar for mackerel, Cochin for prawn and at Madras for moUuscan fisheries. Programmes of work undertaken at the various centres of study were actively continued